PERAN KELUARGA DALAM PENCEGAHAN KENAKALAN REMAJA GENG MOTOR - Lani Pranesti; Alfalah Putri Nura'raafa; Yuarini Wahyu Pertiwi (CV. ADIBA AISHA AMIRA, 2024)
Juvenile delinquency involved in motorbike gangs is widespread. The activities of this motorbike gang are dominated by bad activities such as brawls between motorbike gang groups or activities that disturb residents. This research aims to look at the factors that cause teenagers to join motorbike gangs, as well as to look at the role and prevention that can be done by families in dealing with juvenile delinquency involved in motorbike gangs. The research method used is through literature study. The results of this study show that the factors causing delinquency in teenagers involved in motorbike gangs are due to family environmental factors and also environmental factors. Prevention that can be done is by implementing the role of the family which functions as an educator, motivator, good listener and as a supervisor.